Non-innocent behaviour of imido ligands in the reactions of silanes with half-sandwich imido complexes of Nb and V: a silane/imido coupling route to compounds with nonclassical Si--H interactions. - Ignatov, S; Rees, N; Merkoulov, A; Dubberley, SR; Razuvaev, A; Mountford, P; Nikonov, G (2008)
Reactions of imido complexes [M(Cp)(=NR')(PR''3)2] (M=V, Nb) with silanes afford a plethora of products, depending on the nature of the metal, substitution at silicon and nitrogen and the steric properties of the phosphine. The main products are [M(Cp)(=NR')(PR3)(H)(SiRnCl3-n)] (M=V, Nb; R'=2,6-diisopropylphenyl (Ar), 2,6-dimethylphenyl (Ar')), [Nb(Cp)(=NR')(PR''3)(H)(SiPhR2)] (R2=MeH, H2), [Nb(Cp)(==NR')(PR''3)(Cl)(SiHRnCl2-n)] and [Nb(Cp)(eta 3-N(R)SiR2--H...)(PR''3)(Cl)]. Complexes with the smaller Ar' substituent at nitrogen react faster, as do more acidic silanes. Bulkier groups at silicon and phosphorus slow down the reaction substantially. Kinetic NMR experiments supported by DFT calculations reveal an associative mechanism going via an intermediate N-silane adduct [Nb(Cp){=N(-->SiHClR2)R'}(PR''3)2] bearing a penta-coordinate silicon centre, which then rearranges into the final products through a Si--H or Si--Cl bond activation process. DFT calculations show that this imido-silane adduct is additionally stabilized by a Si--HM agostic interaction. Si--H activation is kinetically preferred even when Si--Cl activation affords thermodynamically more stable products. The niobium complexes [NbCp(=NAr)(PMe3)(H)(SiR2Cl)] (R=Ph, Cl) are classical according to X-ray studies, but DFT calculations suggest the presence of interligand hypervalent interactions (IHI) in the model complex [Nb(Cp) (==NMe)(PMe3)(H)(SiMe2Cl)]. The extent of Si--H activation in the beta-Si--HM agostic complexes [Cp{eta 3-N(R')SiR2--H}M(PR''3)(Cl)] (R''=PMe3, PMe2Ph) primarily depends on the identity of the ligand trans to the Si--H bond. A trans phosphine leads to a stronger Si--H bond, manifested by a larger J(Si--H) coupling constant. The Si--H activation diminishes slightly when a less basic phosphine is employed, consistent with decreased back-donation from the metal.